CULTURAL STUDIES: STUDENTS’ LEARNING STYLE BASED ON MALE AND FEMALE AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Sartika Sartika; Ingriyani Yohana Rawung; Yuliana Daeng Macora (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
This research aimed to determine the learning styles used by male and female students in fourth, sixth and eighth semesters at the English Language Education Study Program. The research was conducted at Sintuwu Maroso Poso University. The method used in this research is descriptive qualitative research. The research subjects were 45 students of the English Language Education Study Program. The instruments used to collect data are questionnaire and interview. The results showed that there were six learning styles used by students in fourth, sixth and eighth semeters at the English Language Education Study Program, namely visual, auditory, kinesthetic, tactile, group and individual learning styles. The dominant learning style used by male students at the English Language Education Study Program was the group learning style with an average number 37.7, while the dominant learning style used by female students at the English Language Education Study Program was the kinesthetic learning style with an average number 39.5.